MODERNISASI PENDIDIKAN ISLAM DI INDONESIA - Saihu Saihu (Al Amin: Jurnal Kajian Ilmu dan Budaya Islam, 2018)
Pioneer of Islamic education changes toward a modernization education especially religion school (Islamic Education), first originated by colonialism governance in this case is Holland  that built people school, secondly originated from Islamic Reformis Bachelor they have been finished their studied in Mecca Saudi Arabia. Need we know that an institutions of Islamic education such as pesantren or surau initially using a traditional method and there is no classical but after Islamic bachelors back home to Indonesia their built a system and modern method that an education must be there a class, grade, goal, and curriculum etc. furthermore most of Islamic Education using a modern system all of the devices of them, but there was a little of them still implemented a traditional method its depends on of the material.